THE DESIGN FEATURES OF THE COMPOUND FEED DISPENSER FOR DAIRY ROBOTIC MILKING SYSTEMS BY GEA - Buhay, Tatiana; Hnoievyі Ihor; bezuhlyi, mykola; Shigimaga, Victor (European Science, 2023)
High-yielding cows are at risk of carbohydrate poisoning because they get concentrated feed as part of the main diet on the feed table, as well as from the milking system. In order to reduce the risk of overfeeding cows, the ways to improve feed dispenser